Odpowiedzi

2010-02-07T18:00:44+01:00
A) 2(x² - 2x + 3) - 2(x² - 5x - 1)=
2(2²-2*2+3)-2(2²-5*2-1)=
2(4-4+3)-2(4-10-1)=
2*3-2*(-7)=
6+14=
20

b) a(2ab + b) - b(1 - 2ab + a²)=
0,1*(2*0,1*-10+(-10))-(-10)(1-2*0,1*(-10)+0,1²)=
0,1*(0,2-10-10)+10*(1-0,2*(-10)+0,01)=
0,1*(-19,8)+10*(1+2+0,01)=
-1,98+10*3,01=
-1,98+30,1=
28,12
2010-02-07T18:02:22+01:00
A)2*(2²-2*2+3)-2*(2²-5*2-1) = 2*(4-4+3)-2*(4-10-1) = 2*3-2*(-7)=6+14=20
b)0,1*(2*0,1*10+10) - 10*(1-2*0,1*10+0,1²) = 0,1*(0,1+10) - 10*(1-0,1+0,01) = 0,1*10,1-10*0,91=1,01-9,91= -8,9